Optimal scheduling of integrated energy systems with exergy and demand responsiveness - Zhang, Baorui; Wang, Ruiqi; Wang, Ming; Wang, Mingyuan; Li, Ke; Yan, Yi; Gao, He (Frontiers in Energy Research, 2023)
To fairly use demand response to regulate customer load and support the economic and environmental protection, quantity and quality synergistic growth of integrated energy system (IES), a multi-objective optimum scheduling model and solution method taking exergy efficiency and demand response are presented. To begin, a mathematical model of each energy gadget is created. The electric-gas load demand response model is then built using the price elasticity matrix, while the cooling load demand response model is built with the user's comfort temperature in mind. On this basis, a multi-objective optimal dispatching model is developed with the optimization goals of minimizing system operation costs, reducing carbon emissions, and increasing exergy efficiency. Finally, the model is solved using the NSGA-II algorithm to produce the Pareto optimal frontier solution set under various situations, and the VIKOR decision procedure is utilized to identify the complete best dispatching solution. The simulation results suggest that the proposed model can match the system's scheduling needs in terms of numerous objectives such as economy, environmental protection, and exergy efficiency, while also assuring user comfort.